Critical capabilities and competencies for knowledge organizations - Garcia-Perez, Alexeis; Cegarra-Navarro, Juan Gabriel; Bedford, Denise; Thomas, Margo; Wakabayashi, Susan (Emerald Publishing Limited, 2019)
Failed knowledge management projects have one element in common: they fail to focus on the organization's core business functions and instead choose functions that are easy or might produce 'low-hanging fruit'. As a result, often even successful knowledge management projects add little value to the organization as they fail to address the pain points of the heart of the business. So how can knowledge management professionals position themselves for greatest success? In this practical guide, expert authors Alexeis Garcia-Perez, Juan Gabriel Cegarra-Navarro, Denise Bedford, Margo Thomas, and Susan Wakabayashi demonstrate how professionals can map knowledge resources to support business critical capabilities, and increase the impact of knowledge management projects. They also explain how to avoid investing in resources with low value, and how to develop strategies and action plans for different types of resources. Providing practical guidance for professionals, and including mini-case studies of successes and failures, this is an essential book for any knowledge management professional, researcher or student.
Includes index.
Keywords: Knowledge management.; Knowledge management -- Decision-making.; Intellectual capital.; Business & Economics -- Knowledge Capital.; elektronické knihy; electronic books